The Milk of Birds - Whitman, Sylvia (London Atheneum Books for Young Readers, 2013)
When a nonprofit organization called Save the Girls pairs a fourteen-year-old Sudanese refugee with an American teenager from Richmond, Virginia, the pen pals teach each other compassion and share a bond that bridges two continents.
Keywords: Pen pals -- Refugees -- Friendship